SIGNIFICATION OF THE RELATIONSHIP FOR MUSYAROKAH AND MUDHOROBAH FINANCING RESULTS WITH NET PROFIT OBTAINED - R., Rieza; Anam, Moh. (AL-MANSYUR, 2021)
The increasing development of small and medium enterprises, causes the level of economic prosperity of the community to increase. However, this development was not accompanied by sufficient capital, so to increase the capital many companies or business people asked for help from the banking sector. For customers who have expertise, skills and some capital, Islamic financial institutions have types of financing, namely musharakah financing and mudharabah financing. By increasing the level of income, in the end it will increase net profit, then with a large net profit the bank will be able to face great competition as well as market expansion and the continuity of the bank's business will be more guaranteed and the level of income obtained by each product with a comparison that is not too far will make the bank's position is more stable and optimizes profit. To find out the Significance of the Relationship between Musyarokah and Mudharobah Financing Profit Sharing with Net Profits obtained by the Al-Yasini Islamic Financial Institution, namely the more developed al-Yasini Islamic financial institution, because around Rp. 12,000,000.00 net profit obtained by the Al-Yasini Islamic financial institution every month.